Irisin in idiopathic foetal growth restriction - Caglar, Mete; Goksu, Mehmet; Isenlik, Bekir Sitki; Yavuzcan, Ali; Yilmaz, Musa; Ustun, Yusuf; Kumru, Selahattin (Springer, 2014)
Purpose The aim of the present study was to compare maternal serum and cord blood irisin levels in females whose pregnancies were or were not complicated by idiopathic foetal growth restriction. Methods A total of 30 subjects participated. The study group consisted of 15 female patients who were referred to our perinatology clinic for delivery because of foetal growth restriction developing in the third trimester. Fifteen females with uncomplicated singleton pregnancies constituted the control group. Irisin levels were assessed in maternal serum, as well as in serum from the umbilical vein and artery. Results The demographic features of the two groups were similar (p > 0.05). Gestational age at delivery and birth weight were higher in females with uncomplicated pregnancies (p = 0.001). Umbilical artery irisin levels were significantly lower in pregnancies complicated by foetal growth restriction compared to controls (p = 0.003). Umbilical artery irisin levels were positively correlated with foetal weight (p = 0.01) and foetal abdominal circumference (measured by ultrasonography) (p = 0.01). Maternal and umbilical vein irisin levels did not differ between the two groups (p > 0.05). Conclusions The data suggest that umbilical artery irisin levels were lower in pregnancies complicated by foetal growth restriction. Such lower irisin levels may contribute to the pathogenesis of this common condition, and metabolic syndrome may be a long-term consequence of idiopathic FGR.
Keywords: Foetal growth restriction; Fat mass; Irisin; Lean mass; Metabolic syndrome; Umbilical artery